When target CEOs contract with acquirers: Evidence from bank mergers and acquisitions - Elijah Brewer; William E. Jackson; Larry D. Wall (Federal Reserve Bank of Atlanta, 2006)
This paper investigates the impact of the target chief executive officer's (CEO) postmerger position on the purchase premium and target shareholders' abnormal returns around the announcement of the deal in a sample of bank mergers during the period 1990-2004. We find evidence that the target shareholders' returns are negatively related to the postmerger position of their CEO. However, these lower returns are not matched by higher returns to the acquirer's shareholders, suggesting little or no wealth transfers. Additionally, our evidence suggests that the target CEO becoming a senior officer of the combined firm does not boost the overall value of the merger transaction.
Keywords: G34; K22; J33; 330; merger; acquisition; target CEO; corporate governance